THE APPLICATION OF FORWARD CHAINING METHOD TO DETERMINE THE SUITABILITY OF PALAWIJA CROPLAND BASED ON GIS WEB - Agarina, Melda; wahyuni, Tri (Prosiding International conference on Information Technology and Business (ICITB), 2016)
Crops or second crop after rice, usually planted by residents when the water is not sufficient to grow rice, in addition to requiring a long time rice requires a lot of water, while crops are not, crops can be grown only by water every day, or not at all depending on soil moisture itself. Dryland farmers in Lampung are always faced with crop failure due to land resources have not been exploited to the maximum such as climate, soil type, rainfall, humidity, and others.Suitability determination system of crop land is intended to facilitate the farmers to get information about the suitability of land crops. Method development in these applications using the System Development Life Cycle Waterfall model which has several stages, namely, planning, analysis, design, implementation and sistem.Penelitian produces a detection system of crop land suitability for web-based so that farmers can get information anywhere and anytime effectively and efficiently. KEY WORDS: Land Suitability, Forward Chaining, Plant Crops